Counterproductive work behaviour among non-teaching staff of a state-owned University: Job characteristics and organizational support in perspective - Uchir, Joseph T.; Ucho, Aondoaver; Gwambe, Christabel D. (Journal of Psychology and Allied Disciplines, 2023)
Counterproductive work behaviour has become a prominent topic of study among organizational behaviour scholars in the 21st Century. This is probably because of the observable impact it has on organizational productivity. This study investigated the influence job characteristics and perceived organizational support have on counterproductive work behaviour among non-teaching staff of a state-owned university in Northcentral, Nigeria A total of 289 participants (204 males and 85 females) took part in the study. Results of Standard Multiple Regression analysis showed that, there was a significant joint positive influence of autonomy, task identity, skill variety, task significance and feedback on counterproductive work behaviour. There was a significant independent positive influence of autonomy and significant negative influence of feedback on counterproductive work behaviour. The study also revealed a significant joint positive influence of job characteristics and perceived organizational support on counterproductive work behaviour and significant negative influence of perceived organizational support on counterproductive work behaviour. It was recommended among other things that universities in Nigeria and other similar institutions should embark on job enrichment drives that provide the pertinent job characteristics such as feedback and support in the workplace.